Formation of ultra-flexible, conformal, and nano-patterned photonic surfaces via polymer cold-drawing. Issue 17 (9th April 2018) - Li, Kaiwei; Zhang, Nan; Zhang, Ting; Wang, Zhe; Chen, Ming; Wu, Tingting; Ma, Shaoyang; Zhang, Mengying; Zhang, Jing; U. S., Dinish; Shum, Perry Ping; Olivo, Malini; et al.
Abstract : Large-area nano-patterning on ultra-thin substrates through mechanical stretching for ultra-flexible and conformal sensors. Abstract : We report a lithography-free method for large-area plasmonic nano-patterning on ultrathin plastic films through a polymer cold-drawing process. We further transfer the ultra-flexible nano-patterned films onto the curved surfaces of plant leaves and apples to work as conformal SERS sensors.